Planting of Discipline Character Education Values in Basic School Students - Fadillah Annisa (Postgraduate School, Universitas Negeri Padang, 2019)
Abstract This study aims to describe the implementation of disciplinary character education in elementary schools and is expected to be able to find policies that support the success of character education. This type of research uses a qualitative approach. The study was conducted at SDN 29 Lubuk Alung, with the subject of principals, teachers, and students. Data is collected through observation, interviews, and documentation. The technique of checking the validity of the data used is the triangulation technique. The results showed that in carrying out disciplinary character education at SDN 29 Lubuk Alung carried out through six policies, namely (1) making character education programs, (2) establishing school rules and class rules, (3) doing Dhuha prayer and Dhuhur prayer in congregation, ( 4) make affective posts in each class, (5) monitor the discipline behavior of students at home through a daily activity notebook, (6) involve parents (7) involving the school committee.Keywords: Discipline Character Education, Elementary School